Mitochondrial oxysterol biosynthetic pathway gives evidence for CYP7B1 as controller of regulatory oxysterols. Issue 189 (May 2019) - Kakiyama, Genta; Marques, Dalila; Takei, Hajime; Nittono, Hiroshi; Erickson, Sandra; Fuchs, Michael; Rodriguez-Agudo, Daniel; Gil, Gregorio; Hylemon, Phillip B.; Zhou, Huiping; Bajaj, Jasmohan S.; Pandak, William M.
Highlights: Cyp27a1 is capable of metabolizing cholesterol to three vital regulatory oxysterols. A new mitochondrial-initiated hepatic pathway of oxysterol/bile acid synthesis. 24HC is metabolized to bile acids via both Cyp7b1 and an independent pathway. Cyp7b1 is a key regulator of the levels of the Cyp27a1 generated oxysterols. Oxysterols are key mediators of cholesterol and lipid homeostasis. Abstract: The aim of this paper was to more completely study the mitochondrial CYP27A1 initiated acidic pathway of cholesterol metabolism. The mitochondrial CYP27A1 initiated pathway of cholesterol metabolism (acidic pathway) is known to synthesize two well-described vital regulators of cholesterol/lipid homeostasis, (25R)-26-hydroxycholesterol (26HC) and 25-hydroxycholesterol (25HC). Both 26HC and 25HC have been shown to be subsequently 7α-hydroxylated by Cyp7b1; reducing their regulatory abilities and furthering their metabolism to chenodeoxycholic acid (CDCA). Cholesterol delivery into the inner mitochondria membrane, where CYP27A1 is located, is considered the pathway's only rate-limiting step. To further explore the pathway, we increased cholesterol transport into mitochondrial CYP27A1 by selectively increased expression of the gene encoding the steroidogenic acute transport protein (StarD1). StarD1 overexpression led to an unanticipated marked down-regulation of oxysterol 7α-hydroxylase (Cyp7b1), a marked increase in 26HC, and the formation of a third vital regulatory oxysterol, 24( S )-hydroxycholesterol (24HC), in B6/129 mice livers. To explore the further metabolism of 24HC, as well as, 25HC and 26HC, characterizations of oxysterols and bile acids using three murine models (StarD1 overexpression, Cyp7b1 −/−, Cyp27a1 −/− ) and human Hep G2 cells were conducted. This report describes the discovery of a new mitochondrial-initiated pathway of oxysterol/bile acid biosynthesis. Just as importantly, it provides evidence for CYP7B1 as a key regulator of three vital intracellular regulatory oxysterol levels.